الكساد الاقتصادي من وجهة نظر وضعية وإسلامية دراسة مقارنه وصفية. - Khalil Ibrahim, Mehrah Ibrahim; Abdel Salam, El Fatih Abdullahi (Al Hikmah Research and Publication Centre., 2019)
يهدف البحث إلى تسليط الضوء على موضوع المقارنة بين إسهامات النظرة الشرعية الإسلامية والوضعية ومدى قدرتهما على علاج مشكلة الكساد الاقتصادي، حيث تحاول الدراسة إلى توعية المؤسسات والمسؤولون والناس بشكل عام حول أهمية التفكر وإدراك مدى عظم هذه المشكلة والبحث عن بعض الحلول الممكنة؛ ليعيش العالم بأمان واستقرار. تم التعرف في البحث على مفهوم الكساد الاقتصادي، وبيان الأسباب التي أدت إلى حدوث الكساد الاقتصادي، وكذلك النتائج التي تترتب على حدوثه، كما تم التعرف على طرق الوقاية منها من وجهة نظر علماء اقتصاد الوضعية وعلماء اقتصاد الإسلامية، ومن ثم اقتراح مجموعة من الحلول التي يمكن أن تساهم في تقليل والوقاية من حدوث الكساد الاقتصادي. وقد اتبعت الباحث مجموعة من المنهجيات العلمية التي تناول بها موضوعه، فمن خلال المنهج الوصفي قام الباحث بوصف أسباب حدوث الكساد الاقتصادي، ثم من خلال المنهج المقارن عقدت الباحث مقارنة بين حلول من وجهة نظر الوضعية ومن وجهة نظر إسلامية، وكذلك قامت بإجراء بعض المقابلات الشخصية مع بعض اقتصاديين والفقهيين لمعرفة رأيهم حول ذلك. وخلصت الدراسة بمجموعة من النتائج من أهمها: ذكرت الباحثة العديد من الحلول من وجهة نظر الوضعين، فتطرقت إلى حلين وهما زيادة الاستهلاك وسياسية التمويل بالعجر، فترى أن الوضعيين في هذا الحلين كأنهم اتجهوا لحل مشكلة الكساد من ناحية إسلامية، فعند الحديث عن زيادة الاستهلاك كانوا يقدمون الإعانات للطبقة الفقيرة، ليتمكنوا من الصرف ويتعدل وضعهم، ومن ناحية سياسة التمويل بالعجز تخصص الحكومات مبالغ للنفقات العامة تغطي بها العجز في الميزانية، أما عن طريق الاقتراض من الأفراد أو البنك المركزي حيث يصدر للحكومات كميات إضافية من النقود. فترى أن الموقف من وجه نظرها هو موقف إنساني عظيم ولكن بشرط الضبط الدقيق ومراعاة الأوضاع عند اتباع سياسة التمويل للعجز لكيلا نقع في مشاكل أخرى، ولاحظت من الحلين كأنهم يتبعون طريقة الصدقات من ناحية التبرع والرغبة في تحقيق عدالة التوزيع المتبعة في الدول الإسلامية من حلولهم، كما ختمت الباحثة بمجموعة من التوصيات. **************************************************************************************** The research aims to shed light on the issue of comparing the contributions of the Islamic Shariahbased economy and the positive economy approaches and their ability to deal with the problem of economic depression. The study tries to raise awareness among institutions, officials and the people in general about the importance of thinking and understanding the extent of this problem and searching for some possible solutions so that security and stability prevail in the world. The research has identified the concept of economic depression, its causes and consequences. The methods of prevention have also been identified from the point of view of positive economists and Islamic economists, and a set of solutions that can contribute to preventing economic depression or reducing its impact also have been identified. The researcher followed a set of scientific methodologies in dealing with the subject. Through the descriptive approach, the researcher described the causes of economic depression, and then through the comparative method, the researcher compared the solutions from a positive economic point of view as well as from an Islamic economic point of view. She also conducted interviews with a number of economists and jurisprudents to know their opinion about those solutions. The study came up with a set of conclusions. Most importantly, the researcher mentioned a number of solutions from a positive point of view and dealt with two such solutions, namely increasing consumption and the policy of financing through deficit. The researcher found out that by suggesting these solutions, positive economists tended to solve the problem of depression from an Islamic point of view. In proposing an increase in consumption, they suggest providing subsidies to the poor to enable them to spend and thus change their status. As for, financing through deficit, they propose that governments allocate funds for public spending to cover budget deficit, either through borrowing from the public or the central bank, where the government can issue additional amounts of money. From the researcher's point of view, this is a great humanitarian position, provided it is carefully monitored and the general situation is taken into account when adopting it so that we do not face other problems. The researcher noticed that the two solutions are seen as following the Islamic charity concept in terms of donation and the desire to follow the example of Islamic countries in realizing justice in distribution. The researcher concluded with a set of recommendations.